Long‐term safety and efficacy of trifarotene 50 μg/g cream, a first‐in‐class RAR‐γ selective topical retinoid, in patients with moderate facial and truncal acne. (20th August 2019) - Blume‐Peytavi, U.; Fowler, J.; Kemény, L.; Draelos, Z.; Cook‐Bolden, F.; Dirschka, T.; Eichenfield, L.; Graeber, M.; Ahmad, F.; Alió Saenz, A.; Rich, P.; Tanghetti, E.
Abstract: Background: Treatment for both facial and truncal acne has not sufficiently been studied. Objectives: To evaluate the long‐term safety and efficacy of trifarotene in both facial and truncal acne. Methods: In a multicentre, open‐label, 52‐week study, patients with moderate facial and truncal acne received trifarotene 50 μg/g cream (trifarotene). Assessments included local tolerability, safety, investigator and physician's global assessments (IGA, PGA) and quality of life (QOL). A validated QOL questionnaire was completed by the patient at Baseline, Week 12, 26 and 52/ET. Results: Of 453 patients enrolled, 342 (75.5%) completed the study. Trifarotene‐related treatment‐emergent adverse events (TEAEs) were reported in 12.6% of patients, and none was serious. Most related TEAEs were cutaneous and occurred during the first 3 months. Signs and symptoms of local tolerability were mostly mild or moderate and severe signs, and symptoms were reported for 2.2% to 7.1% of patients for the face and 2.5% to 5.4% for the trunk. Local irritation increased during the first week of treatment on the face and up to Weeks 2 to 4 on the trunk with both decreasing thereafter. At Week 12, IGA and PGA success rates were 26.6% and 38.6%, respectively. Success rates increased to 65.1% and 66.9%, respectively at Week 52. Overall success (both IGA and PGA success in the same patient) was 57.9% at Week 52. At Week 52 visit, 92/171 (53.8%) patients who had completed their assessments had scores from 0 to 1 (i.e. no effect of acne on their QOL) vs. 47/208 (22.6%) patients at Baseline visit. Conclusion: In this 52‐week study, trifarotene was safe, well tolerated and effective in moderate facial and truncal acne.